Extending the Studentsâ€™ Narrative Text Comprehension through Reading SMART Protocol - Fachri Ardiansyah; Aswadi Jaya (Universitas PGRI Palembang, 2020)
Abstract: The problem of this study was â€œis there any significant difference on studentsâ€™ reading achievement in learning narrative text to the tenth grade students of state vocational high school 1 Palembang who are taught through smart technique and those who are not?â€. The main objective of this study was to find out whether or not there is any significant difference on studentsâ€™ reading achievement in learning narrative texts to the tenth grade students of state vocational high school 1 Palembang who are taught through smart technique and those who are not. This study applied a Quasi Experimental Designs. The population was the Tenth grade students at State Vocational High School Palembang with the total number of the 389 students. The sample was 60 students. They were 30 students from X AKL 1 as control group and X AKL 2 as experimental group taken by using Purposive Random Sampling. The data were collecting by using a written test with multiple choice questions and analyzed by using Independent t-test. The result of the study showed that the studentsâ€™ average score in control group in pre-test was 35.07 and in post-test was 47.04 and in experimental group in pre-test was 55.54 and in post-test was 84.54. The value of t-obtained 4.951 was higher than the value t-table 1.669, at the significant level 0.05 in two - tailed with df=64, It is found that there was significant difference on the tenth grade studentsâ€™ reading achievement between those who are taught through Smart Technique and those who are not of State Vocational High School 1 Palembang.Keywords: Teaching, Reading, Narrative Text, and Smart Technique.